POSISI DESA SERANGAN BERDASARKAN ANALISIS TOURISM AREA LIFE CYCLE - Suryaningsih, Ida Ayu Anggreni; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2016)
Abstract In the development of a tourist area, especially the development of tourism will generally follow the pattern of grooves or tourism area life cycle is known as the Tourism Area Life Cycle (TALC). This paper aims to find a position that tourism in Serangan Village, so it can later be known by both programs suitable for the development of the area. The needs of the data used to meet, namely, observation, literature review and interviews with some of the residents and community leaders in the village attack. The collected data will be described later analyzed by descriptive. Observations show that the position of the Serangan Village in Tourism Area Life Cycle analysis is at a stage 2 or the stage engagement (involvement). In this phase, the increase in the number of tourist arrivals in the Serangan village has increased every year and the local people who were there already started to supply the needs of tourists as a cafe or restaurant and homestay but still on a limited scale. Local people have started actively promoting in several blogs and web is also working with several travel agents. The creation of a forum for the community to develop into a more concerted Serangan village to be planned future namely the formation of a group of fishermen who called Karya Segara. The group is very active fishing village of attacks and protecting the environment are very enthusiastic about the preservation of underwater attack. Starting from the initiative group of fishermen began to attack this village known and increasingly shows its uniqueness in terms of environmental conservation. This it can be concluded that the position of the Serangan Village in Tourism Area Life Cycle analysis is in phase engagement (involvement) were associated with the facts on the ground.
Keywords: Tourism Area Life Cycle, the position of tourism, local communities.